REVOLUTIONIZING EDUCATIONAL SUCCESS THROUGH STRATEGIC HRM PRACTICES - Ahmad Hajam, Aajaz (Журнал математики и информатики, 2024)
This study investigates the strategic impact of Human Resource Management (HRM) practices on enhancing educational outcomes in academic institutions, focusing on three key areas: teacher recruitment, retention, and professional development. Amidst the evolving educational landscape, HRM plays a crucial role in addressing challenges such as high turnover rates, the integration of digital tools in education, and the alignment of institutional goals with workforce capabilities. By conducting a comprehensive review of literature and empirical studies, this research identifies significant discrepancies between the theoretical understanding of effective HRM practices and their practical implementation. The findings reveal that institutions leveraging advanced digital recruitment strategies, robust support systems, and personalized professional development programs report better teacher retention, higher job satisfaction, and improved educational effectiveness. Recommendations are made for schools to adopt more integrated and responsive HRM approaches to overcome sector-specific challenges and enhance overall institutional performance, thereby contributing to superior educational outcomes.